2018
DOI: 10.1002/hpm.2616
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to reporting of patient safety incidents in tertiary hospitals: A qualitative study of nurses and resident physicians in South Korea

Abstract: We explored the barriers to reporting patient safety incidents experienced by nurses and resident physicians while working in tertiary hospitals in South Korea. Sixteen in-depth interviews with 10 nurses and 6 resident physicians, all of whom had experienced patient safety incidents, were conducted. The interviews were analyzed using directed content analysis in accordance with a coding scheme developed in this study, which contains 4 categories (incidents and reporters, reporting procedures and systems, feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…Additionally, leaders were identified as the entity that played a crucial role in building culture, similar to the previous studies that emphasized the role of leaders. 21 22 26 Insufficient human resources, excessive workload, and poor work environments were identified as factors that interfered with patient safety. Therefore, human and material support are essential for improving PSC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, leaders were identified as the entity that played a crucial role in building culture, similar to the previous studies that emphasized the role of leaders. 21 22 26 Insufficient human resources, excessive workload, and poor work environments were identified as factors that interfered with patient safety. Therefore, human and material support are essential for improving PSC.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring duty hour restrictions was a major aim of the Medical Resident Act and a major controversial issue. With the passing of the legislation, concerns were raised that it would be too difficult to reduce training physicians’ working hours given practical circumstances, such as general hospitals with an excessive patient load or smaller institutions with chronic workforce shortages [ 11 ]. However, the above results showed that working conditions gradually began to comply with the new standards, with more full days off-duty and guaranteed vacation time.…”
Section: Discussionmentioning
confidence: 99%
“…The recent global pandemic has reinforced the view that universal access to public health and care systems needs to be prioritized, and that our representative democracy with its polarized views regarding science and expertise may be ineffective in handling new patterns of risk and uncertainty [1][2][3][4]. Since the late 1990s, the regulation of risks to patients in the health and social care sector has come under severe scrutiny in many countries [5,6] The incident reporting and learning system (IRL) was adopted in healthcare organizations, and became one of the major policy measures [7][8][9][10][11][12][13][14], following other safety-critical industries such as nuclear power, offshore oil exploration and aviation [15]. This safety information system normally relies on reports submitted by frontline staff, and contains data that cover near-misses, adverse events and safety concerns.…”
Section: Introductionmentioning
confidence: 99%